2009
DOI: 10.1038/bmt.2009.114
|View full text |Cite
|
Sign up to set email alerts
|

Palonosetron and dexamethasone for prevention of nausea and vomiting in patients receiving high-dose chemotherapy with auto-SCT

Abstract: The aim of this study was to determine the efficacy of palonosetron combined with dexamethasone in prevention of chemotherapy (CT)-induced nausea and vomiting (CINV) in patients receiving high-dose (HD)-CT with auto-SCT, and the efficacy of a second dose of palonosetron in treating breakthrough emesis. One hundred thirty-four patients treated with HD-CT and auto-SCT for hematologic malignancies received palonosetron as prophylaxis for CINV on the first day of conditioning; patients were also administered dexam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…In this trial, dexamethasone was administered throughout the entire treatment period. CR rate was only 36%; however, 50% of the patients were retreated with palonosetron for breakthrough emesis and were successfully rescued [17].…”
Section: High-dose Chemotherapymentioning
confidence: 99%
“…In this trial, dexamethasone was administered throughout the entire treatment period. CR rate was only 36%; however, 50% of the patients were retreated with palonosetron for breakthrough emesis and were successfully rescued [17].…”
Section: High-dose Chemotherapymentioning
confidence: 99%
“…5 Palonosetron prevented nausea and vomiting in 36% of patients undergoing autologous BMT, whereas in another 26% symptom control was achieved following a second dose. 7 In childhood cancers, the optimal schedule of palonosetron has not been established yet. Kadota et al 8 administered the drug at 3 or 10 mg/kg, and found these dosages equieffective and equitoxic.…”
mentioning
confidence: 99%
“…Few prospective, small-size trials assessing multiple dosing schedules of palonosetron in the setting of HDC have been published since enrollment into this trial began [13][14][15][16]. Although these studies suggest that palonosetron for multiple days can be more effective against CINV in patients receiving multiple-day HDC, the optimal dosing schedule of palonosetron in this setting remains to be investigated.…”
Section: Discussionmentioning
confidence: 98%